Development of a model to deliver primary health care in Qatar. Issue 1 (30th December 2020) - Syed, Mohamed Ahmed; Al Mujalli, Hanan; Kiely, Catherine Maria; A/Qotba, Hamda Abdulla
Abstract : Background: Healthcare providers around the world are seeking to manage the rising burden of chronic conditions against a backdrop of both growing and ageing populations as well as greater expectations of health services. This paper describes the development of an integrated primary care model 'the family medicine model (FMM)' to deliver primary healthcare in Qatar to better address some of the healthcare challenges faced. Methods: A developmental approach was adopted in defining an FMM for Qatar that could potentially address health needs of its population, while acknowledging local context and addressing complexities. A literature review was undertaken followed by field visits and setting up of a working group in order to identify, develop and adapt a model suitable for delivery of primary care in Qatar. Results: Key principles of the proposed model and its component were defined. Components included primary care workforce and practice-based teams, service provision and practice-based services, health information and technology, access to care and information, care management, care coordination, practice management and quality and safety. Conclusions: The proposed model is an innovative approach which utilises and integrates these components to deliver holistic primary care. It is anticipated that its introduction will help redesign and integrate the way primary healthcare is delivered to the population of Qatar in helping patients manage their own health and reduce the numbers that need to be admitted to secondary care, improving patients' independence and well-being as well as dramatically reducing the cost to the overall health system.